Effects of micro-drip irrigation on soil enzymatic activities and nutrient uptake, and cucumber (Cucumis sativus L.) yield. Issue 12 (15th October 2021) - Wang, Xiao; Lu, Ping; Yang, Peiling
ABSTRACT: Micro-drip irrigation promotes high water and nutrient use efficiency in crops.We aimed to develop a new micro-drip irrigation technology that can reduce the effects of chemical fertilizer input on soil quality while maintaining agricultural productivity. There were four treatments: micro-drip irrigation with 240 (LF), 300 (MF), and 360 kg ha -1  fertilization (HF) and subsurface drip irrigation (SDI) with 240 kg ha -1  fertilization (CK). Micro-drip irrigation decreased N concentration around the roots by >24% compared with SDI, and increased the urease, alkaline phosphatase activities, and partial nitrogen productivity by 31.5%, 37.7%, and 22.1%, respectively. Although the HF treatment increased cucumber yield by 20%–45% compared with LF and MF, the urease and alkaline phosphatase activities decreased by 11.4%–15.3% and 11.5%–23.0%, respectively. Furthermore, the HF treatment significantly increased the N concentration around the roots. There was a negative correlation between soil enzymatic activities and N concentration. Overall, micro-drip irrigation mitigated the inhibition of soil enzymatic activities and increased nutrient uptake and cucumber yield. However, the negative effects of high fertilization on soil quality and N loss were unavoidable. The optimal fertilization level for greenhouse cucumber cultivations was 300 kg N hm -2  under micro-drip irrigation.